Синхронний метод запису звуку у відеоінтерв’ю - Демиденко, І. Ю. (ХНУРЕ, 2023)
Lapel microphones is better to use for recording interviews. As a recording device, it is better to use a smartphone with a pre-installed voice recorder attachment. During video editing, you can apply time synchronization of the sound of the recorder with the sound of the standard microphone of the video camera. The audio track of the video will be used only as a synchronization signal. A general scheme of sound recording in the studio during interview filming has been developed. This is aimed at recording separate audio tracks of the presenter and guest, as well as backup audio from the recorder and the synchronization track from the video camera
Keywords: відеоінтерв’ю